Scimitar syndrome: A case report - Xiang Zhao; Junyang Huang; Junke Yang; Bingkui Cen (Radiology Case Reports)
Scimitar syndrome is a rare vascular malformation characterized by partial or total abnormal flow of the right pulmonary vein into the inferior vena cava, located above or below the diaphragm. Scimitar syndrome is a rare disease has an incidence of approximately 1-3 per 100,000 live births. And it can be divided into infantile type and child/adult type. Infantile patients have more deformities and poor prognosis, so it is urgent to combine multidisciplinary early precision diagnosis and treatment. Most children with childhood/adult forms are asymptomatic or have mild symptoms and can live normally without medical intervention. Here we report a case of a 3 year, 8-month-old girl who was diagnosed with Scimitar syndrome in our hospital. By presenting multiplanar CT images of malformed drainage veins in this patient's lungs and analyzing a series of cardiopulmonary abnormalities resulting from them, we have demonstrated in detail the diagnostic process of this rare disease, Scimitar syndrome. For patients with Scimitar syndrome, whether to take surgical treatment should be determined according to the specific cardiopulmonary function of patients, mild patients can take regular follow-up strategy. For patients with obvious clinical symptoms, surgery can significantly improve the long-term prognosis.